ANALISIS STRATEGY PRODUKSI, MANPOWER PLANNING DAN PENGELOLAAN LINGKUNGAN TERHADAP PEMASARAN PADA PT. ANGELS PRODUCTS, BOJONAGARA, SERANG, BANTEN - Bomer Pasaribu; Partogi S Samosir; Eddy Sanusi Silitonga; Febriyanti Wulandari; Agus Saputra; Tubagus Arief Budiman; Dirgantoro; Hito Nixon Gozali; Temmy Irvan Gushendra; Nindia Wulandari; Aji Haryanto; Ivan Styo Wibowo; Tulus Mujiantoro; Poppy Dwipuspita; Sara Rastina (SIKAMA : Sinergi Akademisi dan Masyarakat, 2023)
Sugar is a luxury item that is often called white gold and is a staple that is consumed. By the end of 1900, sugar was still a luxury item and was bought by the upper middle class. Over time, sugar can be produced in abundant quantities. Refined crystal sugar is sugar derived from cane juice. In the manufacturing process, sugarcane juice will go through a long refining and processing process so as to produce pure sugar (Raw Sugar). PT. Angels Products is the first refined crystal sugar factory in Indonesia that operated in 1997. PT Angels Products is a company engaged in the refined crystal sugar industry located in banten province. On December 17, 2022, Krisnadwipayana University held a Field Study in order to fulfill the compulsory study program for Master of Management (Strata 2) to PT. Krisnadwipayana. Angels Product is located in Bojonagara District, Serang Regency, Banten. In field study activities, research activities are also carried out with the method of direct visits to the research site and conducting interviews with informants and direct observations. The nature of this research is descriptive qualitative research, which is research conducted based on views, strategies and model implementation by drawing problems based on the findings. Describe the results of interviews and observations so as to get the desired data and analyze it. Research carried out on fiel study activities in the form of production layouts, logistics systems, production process flows, man power planning, production, marketing and environmental management.